2021
DOI: 10.3390/atmos12040425
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter and Associated Metals: A Link with Neurotoxicity and Mental Health

Abstract: Particulate air pollution (PM) is a mixture of heterogenous components from natural and anthropogenic sources and contributes to a variety of serious illnesses, including neurological and behavioral effects, as well as millions of premature deaths. Ultrafine (PM0.1) and fine-size ambient particles (PM2.5) can enter the circulatory system and cross the blood–brain barrier or enter through the optic nerve, and then upregulate inflammatory markers and increase reactive oxygen species (ROS) in the brain. Toxic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Exposure to particulate matter (PM) has been associated with millions of premature deaths each year worldwide. 1–3 According to numerous studies, particulate matter is responsible for a multitude of adverse health risks, including cardiovascular disorders, 4–7 impaired mental health, 8–10 carcinogenic diseases and respiratory problems. 11–15 Due to the considerable differences in chemical composition of ambient particles formed from different emission sources, the PM mass concentration is probably not an ideal measure for the toxicity of PM.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to particulate matter (PM) has been associated with millions of premature deaths each year worldwide. 1–3 According to numerous studies, particulate matter is responsible for a multitude of adverse health risks, including cardiovascular disorders, 4–7 impaired mental health, 8–10 carcinogenic diseases and respiratory problems. 11–15 Due to the considerable differences in chemical composition of ambient particles formed from different emission sources, the PM mass concentration is probably not an ideal measure for the toxicity of PM.…”
Section: Introductionmentioning
confidence: 99%
“…However, ultrafine particles or nanoparticles (PM0.1) has recently become of more concern, because they are more carcinogenic and can cause greater health effect than larger particles because of larger surface area (Sharma and Balasubramanian, 2018;Ajdary et al, 2018;Schraufnagel, 2020). Besides traveling deep into the lung mainly in the alveolar region (Schraufnagel, 2020), PM0.1 can translocate from the cardiopulmonary system to the central nervous system by crossing the blood-brain barrier, and potentially cause brain damage (Cheng etal., 2016;Jew et al, 2019;Morris-Schaffer et al, 2019;Hahad et al, 2020;Potter et al, 2021).…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%
“…For example, PM 2.5 inhalation study in mice found that PM 2.5 -bound metals could reach and gather in secondary off-target tissues (liver, heart and brain) [155]. After intratracheal instillation of mice with coal and coal fly-ash, Cr, Fe and Ni were detected in liver, spleen and brain [156] PM and associated metals have been linked to neurotoxicity and mental health [157]. Excess brain exposure to either essential or non-essential elements can result in brain dyshomeostasis, which has been implicated in both neurodevelopmental disorders (NDDs; autism spectrum disorder, schizophrenia, and attention deficit hyperactivity disorder) and neurodegenerative diseases [158].…”
Section: Translocation Of Inhaled Metals From Lungs To Other Organsmentioning
confidence: 99%